2018
DOI: 10.3390/polym10090942
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics of Polypropylene Mixed with Natural Nanoclay

Abstract: Polypropylene has been used in radio-frequency capacitors and has also started to be employed in cables as insulation. The objective of this study was to evaluate the electrical properties of polypropylene filled with natural clay as a nano-material. Polypropylene samples having 0%, 2% and 6% natural clay by weight were exposed to 60-Hz sinusoidal voltages at two different rates of rise. The breakdown voltage of each sample was recorded at these different ramp rates. Also, the Root-mean-squared (rms) current w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…This phenomenon seems to be different from our expectation of the experiment. In a previous research, nano-fillers have a significant effect on improving the electrical strength of PP films [15]. In the present study the applied electric field intensity was set to a much lower level than the breakdown strength of plain PP and the PP nanocomposite.…”
Section: B Experimental Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…This phenomenon seems to be different from our expectation of the experiment. In a previous research, nano-fillers have a significant effect on improving the electrical strength of PP films [15]. In the present study the applied electric field intensity was set to a much lower level than the breakdown strength of plain PP and the PP nanocomposite.…”
Section: B Experimental Methodsmentioning
confidence: 91%
“…Also, the temperature on the materials was elevated well above the room temperature. Whereas, the study in [15] was done at room temperature to find the breakdown strength of the material when subjected to a voltage with fixed ramp rate.…”
Section: B Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in power systems, in order to avoid unnecessary service interruption, a proper maintenance program can be established to replace the aged material before it fails. Our previous studies have shown that the electrical properties of PP films have been significantly improved by mixing with 2 wt % natural nano-clay [ 20 ]. However, a reduced lifespan of nano-composite has been found under combined electric and temperature field, compared to the unfilled isotactic PP film [ 21 ].…”
Section: Introductionmentioning
confidence: 99%